2021
DOI: 10.3390/ijms22083835
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Gradient Protein 3 and S100 Calcium-Binding Protein P Levels in Different Endometrial Epithelial Compartments May Play an Important Role in Recurrent Pregnancy Failure

Abstract: Recurrent implantation failure (RIF) and recurrent pregnancy loss (RPL) are distressing conditions without effective treatments. The luminal epithelium (LE) is integral in determining receptivity of the endometrium, whereas functionalis glands and stroma aid in nurturing early embryo development. Calcium signalling pathways are known to be of vital importance to embryo implantation and pregnancy establishment, and anterior gradient protein 3 (AGR3) and S100 calcium-binding protein P (S100P) are involved with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The human endometrium contains multiple cell types, each undergo dramatic transformation throughout the menstrual cycle. Our findings highlight the important requirement to explore the specific areas of the human endometrium according to cellular subtypes, as this may provide clinically useful insights when investigating pathologies such as RRF (Wang et al, 2020;Tempest et al, 2021). Understanding the aetiology for different clinical subtypes of RRF will enable us to undertake future functional studies and discover novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The human endometrium contains multiple cell types, each undergo dramatic transformation throughout the menstrual cycle. Our findings highlight the important requirement to explore the specific areas of the human endometrium according to cellular subtypes, as this may provide clinically useful insights when investigating pathologies such as RRF (Wang et al, 2020;Tempest et al, 2021). Understanding the aetiology for different clinical subtypes of RRF will enable us to undertake future functional studies and discover novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 87%
“…RIF is most commonly accepted as the unsuccessful transfer of three or more good quality embryos following in vitro fertilisation (IVF) and affects approximately 10% of women undergoing IVF treatment ( Margalioth et al 2006 , Tempest et al 2021 ). Inadequate endometrial receptivity is said to be responsible for two-thirds of RIF ( Simon & Laufer 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent pregnancy loss (RPL) ( Eshre Special Interest Group et al , 2018 ) is one of the major challenges for clinicians; ∼50% of cases remain unexplained in aetiology, and the management options are limited and poorly understood ( RCOG, 2011 ; El Hachem et al , 2017 ). Many studies have now suggested an association between unexplained RPL and a defective endometrium ( Quenby et al , 2007 ; Hapangama et al , 2008a ; Lucas et al , 2016 ; Ticconi et al , 2019 ; Dimitriadis et al , 2020 ; Tempest et al , 2021 ). Additionally, inadequate endometrial receptivity may be responsible for two-thirds of recurrent implantation failure (RIF), in which there is failure to implant after multiple transfers of good quality embryos using ART ( Hapangama et al , 2008a ; Simon and Laufer, 2012 ; Bashiri et al , 2018 ; Tempest et al , 2021 ).…”
Section: Implications For Endometrial Pathologiesmentioning
confidence: 99%
“…Many studies have now suggested an association between unexplained RPL and a defective endometrium ( Quenby et al , 2007 ; Hapangama et al , 2008a ; Lucas et al , 2016 ; Ticconi et al , 2019 ; Dimitriadis et al , 2020 ; Tempest et al , 2021 ). Additionally, inadequate endometrial receptivity may be responsible for two-thirds of recurrent implantation failure (RIF), in which there is failure to implant after multiple transfers of good quality embryos using ART ( Hapangama et al , 2008a ; Simon and Laufer, 2012 ; Bashiri et al , 2018 ; Tempest et al , 2021 ). These devastating conditions are important reproductive health issues with many unanswered questions, leading to significant emotional and psychological impact for patients and their partners ( De Klerk et al , 2007 ; Koert et al , 2019 ; Voss et al , 2020 ).…”
Section: Implications For Endometrial Pathologiesmentioning
confidence: 99%
“…Recurrent reproductive failure (RRF) encompasses two separate but related conditions, recurrent implantation failure (RIF), and recurrent pregnancy loss (RPL) [ 3 , 5 , 6 , 7 ]. RIF affects around 10% of women undergoing embryo transfers (ETs) during in vitro fertilisation (IVF) treatment [ 8 ], and the generally accepted definition is three or more failed ET attempts [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%